Current collector and preparation method and application thereof

By providing a conductive layer with a disordered porous structure on the surface of the conductive base film of the negative electrode current collector of the lithium-ion battery, the problems of large current collector density and poor bonding force of the electrode material are solved, and the energy density of the battery and the service life are increased.

CN119742373AActive Publication Date: 2025-04-01YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411942390.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The density of the negative electrode current collector of existing lithium-ion batteries is high, which affects the energy density and endurance of the battery. The volume change of silicon-based materials during charging and discharging leads to the material breakage and powderization, reducing the battery life.

Method used

A conductive base film is used as the base material for the current collector, and a first conductive layer is provided on the surface to regulate its morphology to form a conductive layer with a disordered porous structure on the side away from the current collector, reducing the amount of metal and increasing the bonding force between the current collector and the electrode material.

Benefits of technology

The good conductivity of the current collector is achieved, the quality of the current collector is reduced, the energy density of the battery is improved, the bonding force between the current collector and the electrode material is enhanced, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212846800000191
    Figure BDA0005212846800000191
Patent Text Reader

Abstract

The invention discloses a current collector and a preparation method and application thereof. The current collector comprises a conductive base film, a first conductive layer is arranged on the surface of the conductive base film, a porous structure is arranged on the side, away from the current collector, of the first conductive layer, the porous structure is a disordered porous structure, and the thickness of the conductive layer with the porous structure accounts for 50% or below of the total thickness of the first conductive layer. The current collector provided by the invention has the advantages of good conductivity, low sheet resistance, and strong binding power between the current collector and an electrode material. In addition, the current collector is good in appearance and has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a current collector and a preparation method and application thereof. Background Art

[0002] The rapid development of the new energy vehicle industry has further promoted the development of the lithium-ion battery field. As the basic material in the negative electrode current collector of lithium-ion batteries, the performance of copper current collector directly affects the performance and service life of lithium-ion batteries. At present, the negative electrode current collector is mainly copper metal foil, but the density of copper is high, which is not conducive to improving the energy density of the battery and improving the battery's endurance. Compared with traditional current collectors, composite current collectors based on polymer membranes have the characteristics of low cost, light weight, and good internal insulation. These characteristics enable the composite current collector to reduce the cost of the battery and improve the energy density and safety of the battery when used in the battery.

[0003] In addition, most battery negative electrode materials use silicon-based materials. However, during the charging and discharging process, the generation and decomposition of silicon-lithium alloys are accompanied by huge volume changes. This volume change usually causes the silicon particles to break and pulverize, and the negative electrode active material will fall off the electrode sheet, thereby reducing the battery's service life.

[0004] Therefore, it is necessary to develop a new current collector to reduce the energy density of the current collector and improve the bonding strength between the current collector and the electrode material. Summary of the invention

[0005] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a current collector and a preparation method and application thereof. The current collector of the present invention not only has good conductivity, but also can effectively improve the binding force between the current collector and the electrode material, solve the problem that the electrode material is easy to fall off, and can reduce the mass of the current collector, thereby improving the energy density of the battery prepared by using the current collector.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a current collector, which includes a conductive base film, a surface of which is provided with a first conductive layer, the first conductive layer having a porous structure on a side away from the current collector, the porous structure being a disordered porous structure, and the thickness of the conductive layer having the porous structure is less than 50% of the total thickness of the first conductive layer.

[0008] In the present invention, the thickness of the conductive layer with a porous structure is less than 50% of the total thickness of the conductive layer, for example, it can be 50%, 48%, 45%, 42%, 40%, 38%, 36%, 35%, 33%, 30%, 28%, 25%, 22%, 20%, 18%, 16%, 14%, 12%, 10%, 8%, 5% or 3%, etc.

[0009] The present invention uses a conductive base film as a substrate, arranges a first conductive layer on its surface, and regulates its morphology so that it has a disordered porous structure of a specific thickness on the side away from the current collector. This can reduce the amount of metal used while ensuring that the current collector has good conductivity, and effectively improve the bonding strength between the current collector and the electrode material.

[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0011] Preferably, the thickness of the conductive layer having a porous structure accounts for 10%-45% of the total thickness of the conductive layer.

[0012] Preferably, the conductive base film comprises a polymer film and a second conductive layer disposed on the surface of the polymer film, or the conductive base film comprises a polymer film and conductive particles dispersed inside the polymer film. The present invention does not specifically limit the type of conductive particles, for example, they may be carbon nanotubes, carbon nanofibers or carbon black.

[0013] Preferably, the polymer film includes at least one of polyethylene terephthalate (PET), polypropylene (PP), polyimide (PI), polyethylene (PE), polypropylene, polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyphenylene oxide (PPO) and polystyrene (PS).

[0014] Preferably, the first conductive layer and the second conductive layer are independently at least one of a copper layer, an aluminum layer, a copper alloy layer or an aluminum alloy layer.

[0015] Preferably, the thickness of the second conductive layer is 50 nm-100 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, etc. The thickness here refers to the single-side thickness.

[0016] Preferably, the second conductive layer is prepared by magnetron sputtering.

[0017] The advantage of using the magnetron sputtering method to prepare the second conductive layer is that the prepared conductive metal layer has a dense and uniform structure and controllable thickness, and a dense, uniform and thin film layer can be obtained.

[0018] Preferably, a base layer is further included between the polymer film and the second conductive layer, and the base layer is a metal layer, a metal oxide layer or an alloy layer. The bonding force between the base layer and the second conductive layer is better than that between the polymer film and the second conductive layer. Therefore, by providing the base layer, the bonding force to the second conductive layer is improved.

[0019] Preferably, the base metal layer includes at least one of a silicon-aluminum alloy layer, an aluminum oxide layer, a nickel-chromium alloy layer, a metal nickel layer or a metal chromium layer.

[0020] Preferably, the thickness of the base layer is 10 nm-50 nm, for example, it can be 10 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 18 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.

[0021] Preferably, the base layer is prepared by magnetron sputtering. The advantage of using magnetron sputtering to prepare the base layer is that the prepared base metal layer has a dense and uniform structure and controllable thickness, and a dense, uniform and thin film layer can be obtained.

[0022] As a preferred technical solution of the current collector of the present invention, in the conductive layer with a porous structure, the average pore size of the pores is 0.1μm-10μm, for example, it can be 0.1μm, 0.3μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm, preferably 0.5μm-5μm. If the average pore size is too small, the contact surface area between the electrode material and the current collector is small, and the bonding force is limited; and if the average pore size is too large, the mechanical properties of the electrode sheet prepared using the current collector will decrease.

[0023] Preferably, the porosity of the conductive layer with a porous structure is 1%-50%, for example, it can be 1%, 2%, 4%, 5%, 7%, 8%, 10%, 12.5%, 15%, 17%, 20%, 23%, 26%, 30%, 32.5%, 35%, 38%, 40%, 43%, 45%, 46%, 48% or 50%, preferably 20%-40%. When the porosity is too low, the binding force between the current collector and the electrode material is not good; and when the porosity is too high, the conductive performance of the electrode sheet prepared using the current collector will also decrease.

[0024] Preferably, the first conductive layer includes a first copper layer and a second copper layer, the first copper layer is close to the current collector, the second copper layer is far away from the current collector, and the second copper layer has a disordered porous structure.

[0025] Preferably, the thickness d1 of the first copper layer is 350nm-1250nm, for example, it can be 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, 1050nm, 1100nm, 1150nm, 1200nm or 1250nm, etc. Preferably, the thickness d2 of the second copper layer is 0-625nm and does not contain 0, for example, it can be 0.5nm, 1nm, 3nm, 6nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 60nm, 70nm, 80nm, 100nm, 125nm, 150nm, 165nm, 180nm, 200nm, 225nm, 240nm, 260nm, 280nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm or 625nm, etc. Preferably, the first copper layer and the second copper layer are both prepared by a water electroplating method.

[0026] Preferably, on any side of the current collector, the total thickness of the first conductive layer, the second conductive layer and the base layer is 500nm-2000nm, for example, it can be 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, 1050nm, 1100nm, 1150nm, 1200nm, 1250nm or 1300nm, etc., and the preferred total thickness is 800nm-1300nm. When the total thickness is small, the conductivity of the current collector is poor; when the total thickness is large, on the one hand, the production cost of the current collector will increase, and on the other hand, the mechanical properties of the current collector will decrease. It should be noted that the total thickness here refers to the thickness of a single side of the current collector.

[0027] In a second aspect, the present invention provides a method for preparing the current collector as described in the first aspect, comprising the following steps:

[0028] (1) preparing a second conductive layer on the surface of the polymer film to obtain a conductive base film;

[0029] (2) Using the conductive base film as the cathode, a plating solution containing metal ions is used to perform a first water electroplating on the surface of the second conductive layer of the conductive base film. After the first metal-plated layer is formed on the surface of the second conductive layer, the current density is increased to continue the water electroplating, thereby forming a second metal-plated layer on the surface of the first metal-plated layer to obtain a current collector.

[0030] The method of the present invention first prepares a second conductive layer on the surface of the polymer film, which improves the conductivity of the polymer film on the one hand, and on the other hand, can be directly used as a cathode for water electroplating to form a metal coating on its surface.

[0031] The method of the present invention first prepares a first metal-plated layer as a pre-plated layer, and then adjusts the current density to deposit and prepare the second metal-plated layer. The purpose is to: improve the conductivity of the polymer film and prevent the metal-plated layer from being directly burned when a larger current density is directly used for water electroplating. At the same time, when the current density is increased to deposit the second metal-plated layer, a violent hydrogen evolution reaction will occur, and "small holes" will be generated, leaving holes in the second metal-plated layer, which is beneficial to improving the bonding force between the current collector and the electrode material.

[0032] The method of the present invention can reduce the metal dosage of the current collector without adding additional equipment, improve the bonding strength between the prepared current collector and the electrode material, and is conducive to the industrialization of the current collector.

[0033] In the method of the present invention, the thickness of the first copper plating layer and the second copper plating layer can be controlled by adjusting the current density and the water plating time during water plating. In the same water plating time, a smaller current density will result in a thinner plating layer.

[0034] In the method of the present invention, when step (2) continues to perform water electroplating, the difference from the first water electroplating may be that the current density is increased while other preparation parameters remain unchanged, or the current density may be increased while other parameters are selected within the aforementioned limited range of the parameters of the first water electroplating and the specific values ​​are different from those of the first water electroplating.

[0035] Preferably, the polymer film in step (1) is pretreated before magnetron sputtering.

[0036] Preferably, the pretreatment comprises: after degreasing the polymer film, washing it with alcohol and water, and drying it to obtain the pretreated polymer film, wherein the alcohol may be ethanol and the water may be pure water.

[0037] In one embodiment, the polymer membrane is degreased by placing it in acetone.

[0038] As a preferred technical solution of the preparation method of the current collector of the present invention, before preparing the second conductive layer on the surface of the polymer film, a base layer is first prepared on the surface of the polymer film. Preferably, the base layer is prepared by magnetron sputtering. During the preparation process, the target material is a base metal and the power density is 2W / cm 2 -5W / cm 2 (For example, it can be 2W / cm 2 , 2.5W / cm 2 、3W / cm 2 、3.5W / cm 2 , 4W / cm 2 , 4.5W / cm 2 or 5W / cm 2 The flow rate of protective gas is 80mL / min-120mL / min (for example, it can be 80mL / min, 85mL / min, 90mL / min, 95mL / min, 100mL / min, 105mL / min, 110mL / min, 115mL / min or 120mL / min, etc.), the coating vacuum degree is 80Pa-100Pa (for example, it can be 80Pa, 85Pa, 90Pa, 95Pa or 100Pa, etc.), and the temperature of the main roller is -20℃ to 30℃ (for example, it can be -20℃, -10℃, 0℃, 10℃, 20℃, 22℃, 24℃, 26℃, 28℃ or 30℃, etc.).

[0039] Preferably, in step (1), the second conductive layer is prepared by magnetron sputtering, which specifically includes the following steps: placing the polymer film in a magnetron sputtering device and performing magnetron sputtering with a conductive metal target. The polymer film here can be an untreated polymer film, a pretreated polymer film, or a polymer film with a base metal layer formed on its surface.

[0040] Preferably, during the process of preparing the second conductive layer by magnetron sputtering, the power density is 7 W / cm 2 -12W / cm 2 (For example, it can be 7W / cm 2 , 8W / cm 2 , 9W / cm 2 , 9.5W / cm 2 , 10W / cm 2 、10.5W / cm 2 、11W / cm 2 or 12W / cm 2The flow rate of protective gas is 50mL / min-90mL / min (for example, it can be 50mL / min, 55mL / min, 60mL / min, 65mL / min, 70mL / min, 75mL / min, 80mL / min, 85mL / min or 90mL / min, etc.), the coating vacuum degree is 80Pa-100Pa (for example, it can be 80Pa, 85Pa, 90Pa, 95Pa or 100Pa, etc.), and the temperature of the main roller is -20℃ to 30℃ (for example, it can be -20℃, -10℃, 0℃, 10℃, 20℃, 22℃, 24℃, 26℃, 28℃ or 30℃, etc.).

[0041] In the present invention, the type of protective gas is not specifically limited, and for example, it can be at least one of helium, argon or nitrogen.

[0042] As a preferred technical solution of the method for preparing the current collector of the present invention, in the water electroplating method of step (2), the anode is an iridium-plated electrode.

[0043] Preferably, the plating solution comprises: 40 g / L-90 g / L of copper sulfate, 40 g / L-90 g / L of sulfuric acid, and 40 mg / L-70 mg / L of chloride ions. Exemplarily, the concentration of copper sulfate can be, for example, 40g / L, 45g / L, 50g / L, 55g / L, 60g / L, 65g / L, 70g / L, 75g / L, 80g / L, 85g / L or 90g / L, etc.; the concentration of sulfuric acid can be, for example, 40g / L, 45g / L, 50g / L, 55g / L, 60g / L, 65g / L, 70g / L, 75g / L, 80g / L, 85g / L or 90g / L, etc.; the concentration of chloride ions can be, for example, 40mg / L, 42mg / L, 45mg / L, 47mg / L, 50mg / L, 53mg / L, 56mg / L, 58mg / L, 60mg / L, 62mg / L, 65mg / L, 68mg / L or 70mg / L, etc.

[0044] Preferably, the composition of the plating solution includes: 45g / L-70g / L copper sulfate, 40g / L-70g / L sulfuric acid, 50mg / L-60mg / L chloride ions;

[0045] Preferably, the plating solution further comprises at least one of a brightener, a wetting agent and a leveler.

[0046] Preferably, the brightener comprises at least one of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate and sodium N,N-dimethyldithiocarboxamide propane sulfonate.

[0047] Preferably, the wetting agent includes at least one of fatty alcohol polyoxyethylene ether, decene glycol polyoxyethylene ether and sodium dodecyl sulfate.

[0048] Preferably, the leveler includes at least one of benzotriazole, 2-mercaptobenzimidazole, ethylenethiourea and copper tetrahydrothiazolidine sulfide.

[0049] Preferably, in the plating solution, the concentration of the brightener is 3 mg / L-40 mg / L, for example, 3 mg / L, 5 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, 25 mg / L, 30 mg / L, 35 mg / L or 40 mg / L; the concentration of the wetting agent is 5 mg / L-60 mg / L, for example, 5 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, 25 mg / L, 30mg / L, 35mg / L, 40mg / L, 45mg / L, 50mg / L, 55mg / L or 60mg / L, etc.; the leveling agent is 5mg / L-60mg / L, for example, it can be 5mg / L, 10mg / L, 15mg / L, 20mg / L, 25mg / L, 30mg / L, 35mg / L, 40mg / L, 45mg / L, 50mg / L, 55mg / L or 60mg / L, etc.

[0050] Preferably, the temperature of the first water electroplating is 20°C-45°C, for example, it can be 20°C, 22°C, 23°C, 25°C, 28°C, 30°C, 33°C, 36°C, 38°C, 40°C, 43°C or 45°C, etc.

[0051] Preferably, the current density of the first water electroplating is J1, and J1 is 0.1A / dm 2 -2A / dm 2 , for example, it can be 0.1A / dm 2 , 0.3A / dm 2 , 0.5A / dm 2 , 0.7A / dm 2 , 0.8A / dm 2 , 1A / dm 2 , 1.2A / dm 2 , 1.4A / dm 2 , 1.6A / dm 2 , 1.8A / dm 2 or 2A / dm 2 etc., preferably 0.5A / dm 2 -1.5A / dm 2 .

[0052] In the present invention, the unit is A / dm 2 It can be referred to as ASD.

[0053] By controlling the current density of the first water electroplating, a first copper layer with higher density can be obtained.

[0054] Preferably, the current density of the second water electroplating is J2, and J2 is 0.1A / dm 2 -5A / dm 2 , for example, it can be 0.1A / dm 2 , 0.3A / dm 2 , 0.5A / dm 2 , 0.7A / dm 2 , 0.8A / dm 2 , 1A / dm 2 , 1.2A / dm 2 , 1.4A / dm 2 , 1.6A / dm 2 , 1.8A / dm 2 , 2A / dm 2 , 2.3A / dm 2 , 2.6A / dm 2 、3A / dm 2 , 3.2A / dm 2 , 3.4A / dm 2 、3.6A / dm 2 、3.8A / dm 2 , 4A / dm 2 , 4.3A / dm 2 , 4.6A / dm 2 , 4.8A / dm 2 or 5A / dm 2 etc., preferably 2A / dm 2 -4 A / dm 2 By controlling the current density of the second water electroplating, it is possible to ensure that the second plating layer has a suitable average pore size and porosity.

[0055] It should be noted that the higher the current density of the second water electroplating, the better. As the current density of the second water electroplating increases, the number of holes increases, the square resistance of the prepared current collector increases, and the elongation at break and the tensile strength of the current collector decrease to a certain extent.

[0056] Preferably, the difference between J2 and J1 is 2A / dm 2 -3.9A / dm 2 , for example, it can be 2A / dm 2 , 2.2A / dm 2 , 2.4A / dm 2 , 2.6A / dm 2 , 2.8A / dm 2 、3.0A / dm2 , 3.2A / dm 2 , 3.3A / dm 2 , 3.4A / dm 2 、3.5A / dm 2 、3.7A / dm 2 or 3.9A / dm 2 wait.

[0057] The difference between the first current density and the second current density is within the above range, which can ensure the compactness of the first copper layer and meet the realization of the porous structure of the second copper layer, and the bonding force between the current collector and the electrode material is improved.

[0058] As a preferred technical solution of the method for preparing the current collector described in the present invention, the method further includes, after step (2), immersing the prepared current collector in a silane coupling agent solution, immersing for a period of time, washing and drying to obtain a surface-treated current collector.

[0059] Preferably, the concentration of the silane coupling agent solution is 0.5 g / L-3 g / L, for example, it can be 0.5 g / L, 0.8 g / L, 1 g / L, 1.3 g / L, 1.6 g / L, 2 g / L, 2.2 g / L, 2.4 g / L, 2.6 g / L, 2.8 g / L or 3 g / L.

[0060] Preferably, the period of time is 10s-30s, for example, it can be 10s, 12s, 15s, 18s, 20s, 22s, 24s, 26s, 28s or 30s.

[0061] Preferably, the drying temperature is 45°C-75°C, for example 45°C, 47°C, 50°C, 52°C, 55°C, 58°C, 60°C, 65°C, 70°C or 75°C, etc.

[0062] In one embodiment, the present invention provides a method for preparing a current collector, comprising the following steps:

[0063] Step 1: The polymer film is placed in acetone to remove oil, then washed with anhydrous ethanol and pure water, and finally dried to obtain a pretreated polymer film;

[0064] Step 2: Place the pretreated polymer film in a magnetron sputtering device with a silicon-aluminum alloy target (purity: 99.99%) as the target material and a power density of 2W / cm 2 -5W / cm 2 , the argon flow rate is 80mL / min-120mL / min, the coating vacuum is 80Pa-100Pa, the temperature of the main roller is 20℃-30℃, the sputtering thickness is 10nm-20nm, and a thin film with a sputtered base metal layer is prepared;

[0065] Step 3: Place the film with the base metal layer sputtered again in the magnetron sputtering equipment, using a copper target (purity: 99.99%) as the target material and a power density of 7.0 W / cm 2 -12W / cm 2 , the argon flow rate is 50mL / min-90mL / min, the coating vacuum is 80Pa-100Pa, the temperature of the main roller during the coating process is 20℃-30℃, the sputtering thickness is 50nm-100nm, and a film with a sputtered conductive metal layer is prepared;

[0066] Step 4: using deionized water as a solvent and copper sulfate as a copper salt to prepare a plating solution, the composition of the plating solution includes: 40g / L-90g / L of copper sulfate, 50g / L-90g / L of sulfuric acid, 40mg / L-70mg / L of chloride ions, 3mg / L-40mg / L of a brightener, 5mg / L-60mg / L of a wetting agent, and 5mg / L-60mg / L of a leveling agent;

[0067] The film with the sputtered conductive metal layer is placed in a water electroplating device, with the film with the sputtered conductive metal layer as the cathode and the insoluble iridium-plated electrode as the anode, and the film with the sputtered conductive metal layer is subjected to the first water electroplating (current density is 0.1A / dm 2 -2A / dm 2 ), a first copper plating layer is obtained on the surface of the conductive metal layer.

[0068] Step 5: Place the film with the first copper-plated layer prepared in step 4 in a plating solution of the same composition, increase the current density of water electroplating, so that the film is further water-plated on the basis of the first copper-plated layer, and a second copper-plated layer is formed on the surface of the first copper-plated layer to obtain the final prepared current collector.

[0069] In a third aspect, the present invention provides a negative electrode plate, which includes the current collector described in the first aspect and a negative electrode material layer arranged on the surface of the current collector.

[0070] In one embodiment, the negative electrode material layer includes a negative electrode material, a conductive agent, and a binder.

[0071] In one embodiment, the negative electrode material includes, but is not limited to, at least one of artificial graphite, natural graphite, and silicon-based materials.

[0072] In one embodiment, the conductive agent includes at least one of conductive carbon black, graphene, and carbon nanotubes.

[0073] In one embodiment, the binder includes at least one of styrene-butadiene rubber and sodium carboxymethyl cellulose.

[0074] The present invention does not limit the preparation method of the negative electrode sheet, and those skilled in the art may refer to the method disclosed in the prior art for preparation. For example, the preparation may be carried out according to the following method:

[0075] The negative electrode material, the conductive agent and the binder are added into N-methylpyrrolidone, mixed evenly, and then coated onto the surface of the current collector described in the first aspect, and dried to obtain the negative electrode sheet.

[0076] In a fourth aspect, the present invention provides a battery, comprising the negative electrode sheet described in the third aspect.

[0077] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0078] Compared with the prior art, the present invention has the following beneficial effects:

[0079] (1) The present invention uses a conductive base film as a substrate, arranges a first conductive layer on its surface, and regulates its morphology so that it has a disordered porous structure of a specific thickness on the side away from the current collector. This can reduce the amount of metal used while ensuring that the current collector has good conductivity, and effectively improve the bonding strength between the current collector and the electrode material.

[0080] (2) The current collector of the present invention has a tensile strength of more than 232 MPa, an elongation at break of more than 17.8%, a square resistance of less than 25 mΩ, and a binder between the current collector and the electrode material of more than 167 N / m. DETAILED DESCRIPTION

[0081] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0082] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0083] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0084] In the embodiments of the present invention, the thickness refers to the thickness on one side.

[0085] Example 1

[0086] The present embodiment provides a current collector, which includes a conductive base film, the conductive base film includes a polymer film and a base metal layer arranged on both side surfaces of the polymer film, a second conductive metal layer is arranged on the surface of the base metal layer, a first conductive metal layer is arranged on the surface of the second conductive metal layer, the first conductive metal layer includes a first copper layer and a second copper layer, the first copper layer is arranged on the second conductive metal layer, a second copper layer is arranged on the surface of the first copper layer, the second copper layer has a disordered porous structure, a thickness d1 of the first copper layer is 500nm, a thickness d2 of the second copper layer is 400nm, an average pore size of the pores in the second copper layer is 6μm, and the porosity of the second copper layer is 30%.

[0087] The polymer film is polyethylene terephthalate (PET) and has a thickness of 4.5 μm.

[0088] The base metal layer is a silicon-aluminum alloy with a thickness of 15 nm.

[0089] The second conductive metal layer is a copper layer with a thickness of 75 nm.

[0090] This embodiment also provides a method for preparing the above-mentioned current collector, comprising the following steps:

[0091] (1) A biaxially oriented PET film with a thickness of 4.5 μm was placed in 3M acetone for degreasing for 10 min, and then cleaned with a pure water spray pipe for 5 min. The cleaned film was placed in an oven at 60° C. for drying for 20 min. After cooling, a pretreated PET film was obtained.

[0092] (2) The pretreated PET film was placed in a magnetron sputtering device with a silicon-aluminum alloy target (purity: 99.99%) as the target material and a power density of 4 W / cm 2 , the argon flow rate was 100 mL / min, the coating vacuum degree was 90 Pa, the temperature of the main roller was 20°C, and a thin film with a sputtered base metal layer was prepared.

[0093] (3) The film with the base metal layer sputtered is placed in the magnetron sputtering equipment again, with a copper target (purity: 99.99%) as the target material and a power density of 8W / cm 2 , the argon flow rate was 70 mL / min, the coating vacuum degree was 80 Pa, the temperature of the main roller during the coating process was 20°C, and a thin film with the second conductive metal layer sputtered was prepared.

[0094] (4) Deionized water was used as the solvent to prepare a plating solution, the composition of which was: 45 g / L copper sulfate, 70 g / L sulfuric acid, 50 mg / L chloride ion, 5 mg / L sodium polydisulfide propane sulfonate, 10 mg / L fatty alcohol polyoxyethylene ether, and 10 mg / L benzotriazole.

[0095] (5) Place the film with the sputtered conductive metal layer in a water electroplating device, use the film with the sputtered conductive metal layer as the cathode, and use the insoluble iridium-plated electrode as the anode. Control the current density to 0.5A / dm 2 The film after sputtering the conductive metal layer is subjected to the first water electroplating at a temperature of 25° C., and a first copper layer is formed on the surface of the second conductive metal layer to obtain a film after electroplating the first copper layer.

[0096] (6) Place the film after electroplating the first copper layer in a water electroplating device and control the current density to 4A / dm 2 , a second water electroplating is carried out at a temperature of 25°C, so that the film is further thickened by water electroplating on the basis of the first copper layer, and a second copper layer is formed on the basis of the first copper layer. At the same time, due to the high current density during the second water electroplating, holes are left in the second copper layer to obtain a current collector.

[0097] (7) The prepared current collector was immersed in a methanol solution of γ-methacryloxypropyltrimethoxysilane, the concentration of the silane coupling agent solution was 2 g / L, the residence time was 20 s, and after washing with water, it was dried in an oven at 60° C. to finally obtain the current collector.

[0098] Example 2

[0099] The present embodiment provides a current collector, which includes a conductive base film, the conductive base film includes a polymer film and a base metal layer arranged on both side surfaces of the polymer film, a second conductive metal layer is arranged on the surface of the base metal layer, a first conductive metal layer is arranged on the surface of the second conductive metal layer, the first conductive metal layer includes a first copper layer and a second copper layer, the first copper layer is arranged on the second conductive metal layer, a second copper layer is arranged on the surface of the first copper layer, the second copper layer has a disordered porous structure, a thickness d1 of the first copper layer is 350 nm, a thickness d2 of the second copper layer is 220 nm, an average pore size of pores in the second copper layer is 6 μm, and a porosity of the second copper layer is 40%.

[0100] The polymer film is polypropylene (PP) and has a thickness of 5 μm.

[0101] The base metal layer is a nickel layer with a thickness of 25 nm.

[0102] The second conductive metal layer is a copper layer with a thickness of 50 nm.

[0103] This embodiment also provides a method for preparing the above-mentioned current collector, comprising the following steps:

[0104] (1) A 5 μm thick PP film was placed in 2 M acetone for degreasing for 20 min, then cleaned with a pure water spray pipe for 5 min, and the cleaned film was placed in an oven at 70° C. for drying for 15 min. After cooling, a pretreated PP film was obtained.

[0105] (2) The pretreated PP film was placed in a magnetron sputtering device with a nickel target (purity: 99.99%) as the target material and a power density of 2 W / cm 2 , the argon flow rate was 120 mL / min, the coating vacuum degree was 100 Pa, the temperature of the main roller was 25°C, and a thin film with a sputtered base metal layer was prepared.

[0106] (3) The film after sputtering the base metal layer is placed in the magnetron sputtering equipment again, with a copper target (purity: 99.99%) as the target material and a power density of 12W / cm 2 , the argon flow rate was 50 mL / min, the coating vacuum degree was 90 Pa, the temperature of the main roller during the coating process was 30°C, and a thin film with the second conductive metal layer sputtered was prepared.

[0107] (4) Deionized water was used as a solvent to prepare a plating solution, the composition of which was: 60 g / L copper sulfate, 80 g / L sulfuric acid, 60 mg / L chloride ion, 20 mg / L sodium 3-mercapto-1-propane sulfonate, 30 mg / L polyoxyethylene ether of decene glycol, and 60 mg / L 2-mercaptobenzimidazole.

[0108] (5) Place the film with the sputtered conductive metal layer in a water electroplating device, use the film with the sputtered conductive metal layer as the cathode, and use the insoluble iridium-plated electrode as the anode. Control the current density to 1.5 A / dm 2 The film after sputtering the conductive metal layer is subjected to the first water electroplating at a temperature of 20° C., and a first copper layer is formed on the surface of the second conductive metal layer to obtain a film after electroplating the first copper layer.

[0109] (6) Place the film after electroplating the first copper layer in a water electroplating device and control the current density to 4A / dm 2 , a second water electroplating is carried out at a temperature of 25°C, so that the film is further thickened by water electroplating on the basis of the first copper layer, and a second copper layer is formed on the basis of the first copper layer. At the same time, due to the high current density during the second water electroplating, holes are left in the second copper layer to obtain a current collector.

[0110] (7) The prepared current collector was immersed in an ethanol solution of vinyltrimethoxysilane, the concentration of the silane coupling agent solution was 3 g / L, the residence time was 15 s, and after washing with water, it was dried in an oven at 65° C. to finally obtain the current collector.

[0111] Example 3

[0112] The present embodiment provides a current collector, which includes a conductive base film, the conductive base film includes a polymer film and a base metal layer arranged on both side surfaces of the polymer film, a second conductive metal layer is arranged on the surface of the base metal layer, a first conductive metal layer is arranged on the surface of the second conductive metal layer, the first conductive metal layer includes a first copper layer and a second copper layer, the first copper layer is arranged on the second conductive metal layer, a second copper layer is arranged on the surface of the first copper layer, the second copper layer has a disordered porous structure, a thickness d1 of the first copper layer is 600nm, a thickness d2 of the second copper layer is 375nm, an average pore size of the pores in the second copper layer is 5.5μm, and the porosity of the second copper layer is 36%.

[0113] The polymer film is polyethylene terephthalate (PET) and has a thickness of 6 μm.

[0114] The base metal layer is nickel-chromium alloy with a thickness of 40nm.

[0115] The second conductive metal layer is a copper layer, and the thickness of the conductive metal layer is 100 nm.

[0116] This embodiment also provides a method for preparing the above-mentioned current collector, comprising the following steps:

[0117] (1) A 6 μm-thick biaxially oriented PET film was placed in 3M acetone for degreasing for 10 min, then cleaned with a pure water spray pipe for 5 min, and the cleaned film was placed in an oven at 60° C. for drying for 20 min. After cooling, a pretreated PET film was obtained.

[0118] (2) The pretreated PET film was placed in a magnetron sputtering device with a nickel-chromium alloy target (purity: 99.99%) as the target material and a power density of 5 W / cm 2 , the argon flow rate was 80 mL / min, the coating vacuum degree was 80 Pa, the temperature of the main roller was 25°C, and a thin film with a sputtered base metal layer was prepared.

[0119] (3) The film with the base metal layer sputtered is placed in the magnetron sputtering equipment again, with a copper target (purity: 99.99%) as the target material and a power density of 7 W / cm 2 , the argon flow rate was 90 mL / min, the coating vacuum degree was 100 Pa, the temperature of the main roller during the coating process was 25°C, and a thin film with the second conductive metal layer sputtered was prepared.

[0120] (4) Deionized water was used as a solvent to prepare a plating solution, the composition of which was: 90 g / L copper sulfate, 40 g / L sulfuric acid, 70 mg / L chloride ion, 40 mg / L sodium N,N-dimethyldithiocarboxamide propane sulfonate, 50 mg / L sodium dodecyl sulfonate, and 30 mg / L ethylene thiourea.

[0121] (5) Place the film with the sputtered conductive metal layer in a water electroplating device, use the film with the sputtered conductive metal layer as the cathode, and use the insoluble iridium-plated electrode as the anode. Control the current density to 0.6A / dm 2 The film after sputtering the conductive metal layer is subjected to the first water electroplating at a temperature of 25° C., and a first copper layer is formed on the surface of the second conductive metal layer to obtain a film after electroplating the first copper layer.

[0122] (6) Place the film after electroplating the first copper layer in a water electroplating device and control the current density to 3.8A / dm 2 , a second water electroplating is carried out at a temperature of 25°C, so that the film is further thickened by water electroplating on the basis of the first copper layer, and a second copper layer is formed on the basis of the first copper layer. At the same time, due to the high current density during the second water electroplating, holes are left in the second copper layer to obtain a current collector.

[0123] (7) The prepared current collector was immersed in a methanol solution of γ-methacryloxypropyltrimethoxysilane, the concentration of the silane coupling agent solution was 2 g / L, the residence time was 20 s, and after washing with water, it was dried in an oven at 60° C. to finally obtain the current collector.

[0124] Example 4

[0125] This embodiment provides a current collector, which is different from Embodiment 1 in that the thickness of the first copper layer is 400 nm, and the thickness of the second copper layer accounts for 50% of the total thickness of the first copper layer and the second copper layer.

[0126] Example 5

[0127] This embodiment provides a current collector, which is different from Embodiment 1 in that the thickness of the second copper layer is 300 nm. At this time, the thickness of the second copper layer accounts for 37.5% of the total thickness of the first copper layer and the second copper layer.

[0128] Example 6

[0129] This embodiment provides a current collector, and the difference between its preparation method and that of embodiment 1 is that when the second water electroplating is performed in step (6), the current density is controlled to be 5A / dm 2 In the prepared current collector, the porosity of the second copper layer was 48%, and the average pore size of the pores in the second copper layer was 9 μm.

[0130] Example 7

[0131] This embodiment is basically the same as Embodiment 1, except that the thickness of the first copper layer is controlled to be 800 nm, and the thickness of the second copper layer is controlled to be 100 nm, and then the thickness of the second copper layer accounts for 11.1% of the total thickness of the first copper layer and the second copper layer.

[0132] Example 8

[0133] This embodiment is basically the same as embodiment 1, except that: when the second water electroplating is performed in step (6), the current density is controlled to be 3A / dm 2 In the prepared current collector, the porosity of the second copper layer was 20%, and the average pore size of the pores in the second copper layer was 2.5 μm.

[0134] Example 9

[0135] This embodiment is basically the same as Embodiment 1, except that step (2) is not performed in the preparation method, and the current collector does not contain a base metal layer.

[0136] Comparative Example 1

[0137] This comparative example is basically the same as Example 1, except that: when the second water electroplating is performed in step (6), the current density is controlled to be 1.8 A / dm 2 In the prepared current collector, the porosity of the second copper layer was 10%, and the average pore size of the pores in the second copper layer was 1.2 μm.

[0138] Comparative Example 2

[0139] This comparative example is basically the same as Example 1, except that: when the second water electroplating is performed in step (6), the current density is controlled to be 6A / dm 2 In the prepared current collector, the porosity of the second copper layer was 55%, and the average pore size of the pores in the second copper layer was 11 μm.

[0140] Comparative Example 3

[0141] This comparative example provides a current collector, which is different from Example 1 in that the thickness of the second copper layer is 600 nm, and the thickness of the second copper layer accounts for 54.5% of the total thickness of the first copper layer and the second copper layer.

[0142] Comparative Example 4

[0143] This comparative example is basically the same as Example 1, except that the thickness of the first copper layer is 900 nm, and the thickness of the second copper layer is 0.

[0144] Application Examples

[0145] The negative electrode sheets were prepared by using the current collectors prepared in Examples 1-8 and Comparative Examples 1-4, respectively. The preparation method includes the following steps:

[0146] Add negative electrode active materials artificial graphite, conductive carbon black, CMC and SBR to N-methylpyrrolidone, artificial graphite: conductive carbon black: CMC: SBR (mass ratio) = 94:2:2:2, mix evenly and apply it on the current collector, dry and cut to obtain the negative electrode sheet.

[0147] Test and evaluation of current collector:

[0148] ① Tensile strength and elongation at break: The test refers to the national standard GB / T 1040.3-2006. The test results of the present invention are all test data in the MD direction.

[0149] ② Adhesion test: A layer of 3M double-sided tape is bonded to a 3mm thick smooth stainless steel surface. After rolling, the negative electrode is bonded on the double-sided tape, and then a layer of 3M double-sided tape is bonded on the negative electrode. After rolling again, a small strip (150mm×15mm) of ethylene acrylic acid copolymer film is covered on the 3M double-sided tape. Finally, the ethylene acrylic acid copolymer film of the sample strip is fixed to the upper fixture of the tensile machine, and the rest is fixed to the lower fixture. After fixing, the two are peeled at an angle of 90° and a speed of 100mm / min to test the peeling force, that is, the adhesion between the electrode material and the current collector.

[0150] ③ Appearance evaluation: Appearance detection is the most basic and most commonly used detection method. The appearance of the coating is required to be uniform, smooth, free of oxidation discoloration, grease, corrosion, scorch, dendrites and sponges. The present invention uses the visual brightness experience evaluation method to detect the appearance of the current collector. The grading reference standard of the visual brightness experience evaluation method is as follows:

[0151] a. The surface of the first-level (luminous) coating is bright, without oil stains, whitening, burning, etc., and has excellent density;

[0152] b. The secondary (semi-bright) coating is slightly bright, and the surface may be slightly whitened, burnt or other undesirable conditions which can be basically ignored, and the density is good;

[0153] c. Level 3 (dull) coating surface is basically dull, severely burnt, whitened, etc., and has poor density.

[0154] ④ Place the prepared flat current collector sample on the sample table and use a four-probe square resistance meter to test the square resistance of the current collector.

[0155] The test results are shown in Table 1.

[0156] Table 1 Performance test results of current collector and adhesion test results of current collector and electrode material

[0157]

[0158] As can be seen from Table 1, the current collector of the present invention has good conductivity, low sheet resistance, and strong bonding between the current collector and the electrode material. Moreover, the current collector of the present invention has good appearance and excellent mechanical properties.

[0159] By comparing Examples 1, 4, 5, and 7 with Comparative Examples 3 and 4, it can be seen that by controlling the thickness of the second copper layer having a disordered porous structure to account for 10% to 45% of the total thickness of the first copper layer and the second copper layer, the mechanical properties of the current collector can be ensured while improving the adhesion and reducing the square resistance.

[0160] By comparing Examples 1, 6, and 8 with Comparative Example 2, it can be seen that in the process of the second water electroplating in step (6), the current density should not be too large, which may lead to a large porosity and a large average pore size, which is not conducive to improving the mechanical properties and adhesion of the current collector, and will also increase the square resistance, and may even cause the film to be burned. In Example 1, for a thinner magnetron sputtering metal layer, a small current density is first used to prepare the first copper layer, and then the current density is increased to thicken the copper layer, which can improve the ability of the film to withstand a larger current density, and can achieve the purpose of pore formation, and improve the adhesion between the current collector and the electrode material.

[0161] By comparing Example 1 with Comparative Example 1, it can be seen that if the current density during the second water electroplating is small, the porosity will be reduced, and the bonding force between the current collector and the electrode material will be greatly reduced.

[0162] By comparing Example 1 with Example 9, it can be seen that adding a base metal layer is beneficial to improving the mechanical properties and bonding strength of the current collector.

[0163] By comparing Example 1 with Comparative Example 3, it can be seen that when the thickness of the second copper layer is relatively high, the mechanical properties of the current collector will be reduced.

[0164] By comparing Example 1 with Comparative Example 4, it can be seen that when the second copper layer is not provided, the bonding force between the current collector and the electrode material is poor.

[0165] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A current collector, characterized in that: The current collector includes a conductive base film, a first conductive layer is arranged on the surface of the conductive base film, the first conductive layer has a porous structure on the side away from the current collector, the porous structure is a disordered porous structure, and the thickness of the conductive layer with the porous structure accounts for less than 50% of the total thickness of the first conductive layer.

2. The current collector according to claim 1, characterized in that: The thickness of the conductive layer having a porous structure accounts for 10%-45% of the total thickness of the conductive layer; Preferably, the conductive base film comprises a polymer film and a second conductive layer arranged on the surface of the polymer film, or the conductive base film comprises a polymer film and conductive particles dispersed inside the polymer film; Preferably, the polymer film comprises at least one of ethylene terephthalate, polypropylene, polyimide, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide and polystyrene; Preferably, the first conductive layer and the second conductive layer are independently at least one of a copper layer, an aluminum layer, a copper alloy layer or an aluminum alloy layer; Preferably, the thickness of the second conductive layer is 50nm-100nm; Preferably, the second conductive layer is prepared by magnetron sputtering; Preferably, a base layer is further included between the polymer film and the second conductive layer, and the base layer is a metal layer, a metal oxide layer or an alloy layer; Preferably, the base layer comprises at least one of a silicon-aluminum alloy layer, an aluminum oxide layer, a nickel-chromium alloy layer, a metal nickel layer or a metal chromium layer; Preferably, the thickness of the base layer is 10nm-50nm; Preferably, the base layer is prepared by magnetron sputtering.

3. The current collector according to claim 1 or 2, characterized in that: In the conductive layer having a porous structure, the average pore size of the pores is 0.1 μm-10 μm, preferably 0.5 μm-5 μm; Preferably, the porosity of the conductive layer having a porous structure is 1%-50%, preferably 20%-40%; Preferably, the first conductive layer comprises a first copper layer and a second copper layer, the first copper layer is close to the current collector, the second copper layer is far away from the current collector, and the second copper layer has a disordered porous structure; Preferably, the thickness d1 of the first copper layer is 350nm-1250nm; Preferably, the thickness d2 of the second copper layer is 0-625 nm and does not contain 0; Preferably, the first copper layer and the second copper layer are both prepared by water electroplating.

4. The current collector according to any one of claims 1 to 3, characterized in that: On any side of the current collector, the total thickness of the first conductive layer, the second conductive layer and the base layer is 500 nm-2000 nm, preferably 800 nm-1300 nm.

5. A method for preparing a current collector according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) preparing a second conductive layer on the surface of the polymer film to obtain a conductive base film; (2) Using the conductive base film as the cathode, a plating solution containing metal ions is used to perform a first water electroplating on the surface of the second conductive layer of the conductive base film. After the first metal-plated layer is formed on the surface of the second conductive layer, the current density is increased to continue the water electroplating, thereby forming a second metal-plated layer on the surface of the first metal-plated layer to obtain a current collector.

6. The preparation method according to claim 5, characterized in that: Before preparing the second conductive layer on the surface of the polymer film, firstly preparing a base layer on the surface of the polymer film; Preferably, the substrate layer is prepared by magnetron sputtering. During the preparation process, the target material is the substrate metal and the power density is 2 W / cm 2 -5W / cm 2 , the flow rate of protective gas is 80mL / min-120mL / min, the coating vacuum degree is 80Pa-100Pa, and the temperature of the main roller is -20℃ to 30℃.

7. The preparation method according to claim 5 or 6, characterized in that: In step (1), the second conductive layer is prepared by magnetron sputtering, which specifically includes the following steps: placing the polymer film in a magnetron sputtering device and performing magnetron sputtering with a conductive metal target; Preferably, during the process of preparing the second conductive layer by magnetron sputtering, the power density is 7 W / cm 2 -12W / cm 2 , the flow rate of protective gas is 50mL / min-90mL / min, the coating vacuum degree is 80Pa-100Pa, and the temperature of the main roller is -20℃ to 30℃.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In the water electroplating method of step (2), the anode is an iridium-plated electrode; Preferably, the composition of the plating solution includes: 40g / L-90g / L copper sulfate, 40g / L-90g / L sulfuric acid, 40mg / L-70mg / L chloride ions; Preferably, the composition of the plating solution includes: 45g / L-70g / L copper sulfate, 40g / L-70g / L sulfuric acid, 50mg / L-60mg / L chloride ions; Preferably, the plating solution further comprises at least one of a brightener, a wetting agent and a leveling agent; Preferably, the brightener comprises at least one of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate and sodium N,N-dimethyldithiocarboxamide propane sulfonate; Preferably, the wetting agent includes at least one of fatty alcohol polyoxyethylene ether, decene glycol polyoxyethylene ether and sodium dodecyl sulfate; Preferably, the leveler comprises at least one of benzotriazole, 2-mercaptobenzimidazole, ethylenethiourea and tetrahydrothiazolidine copper sulfide; Preferably, in the plating solution, the concentration of the brightener is 3 mg / L-40 mg / L, the concentration of the wetting agent is 5 mg / L-60 mg / L, and the concentration of the leveling agent is 5 mg / L-60 mg / L; Preferably, the temperature of the first water electroplating is 20°C-45°C; Preferably, the current density of the first water electroplating is J1, and J1 is 0.1A / dm 2 -2A / dm 2 , preferably 0.5A / dm 2 -1.5A / dm 2 ; Preferably, the current density of the second water electroplating is J2, and J2 is 0.1A / dm 2 -5A / dm 2 , preferably 2A / dm 2 -4 A / dm 2 ; Preferably, the difference between J2 and J1 is 2A / dm 2 -3.9A / dm 2 .

9. A negative electrode plate, characterized in that: The negative electrode plate comprises the current collector according to any one of claims 1 to 4 and a negative electrode material layer arranged on the surface of the current collector.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Composite current collector and preparation method and application thereof

    CN114284506A

  • Novel bipolar composite current collector and preparation process thereof

    CN117423838A

  • Composite copper current collector with high mechanical property as well as preparation method and application of composite copper current collector

    CN118039919A

  • Current collector for fuel cell

    KR1020110030027A